Em14 II
Em14 II
Em14 II
c W W L Chen, X T Duong and Macquarie University, 1999.
This work is available free, in the hope that it will be useful.
Any part of this work may be reproduced or transmitted in any form or by any means, electronic or mechanical, including
photocopying, recording, or any information storage and retrieval system, with or without permission from the authors.
Chapter 14
INTRODUCTION TO INTEGRATION
14.1. Antiderivatives
In this chapter, we discuss the inverse process of differentiation. In other words, given a function f (x), we
wish to find a function F (x) such that F (x) = f (x). Any such function F (x) is called an antiderivative,
or indefinite integral, of the function f (x), and we write
F (x) = f (x) dx.
A first observation is that the antiderivative, if it exists, is not unique. Suppose that the function
F (x) is an antiderivative of the function f (x), so that F (x) = f (x). Let G(x) = F (x) + C, where C
is any fixed real number. Then it is easy to see that G (x) = F (x) = f (x), so that G(x) is also an
antiderivative of f (x). A second observation, somewhat less obvious, is that for any given function f (x),
any two distinct antiderivatives of f (x) must differ only by a constant. In other words, if F (x) and G(x)
are both antiderivatives of f (x), then F (x) − G(x) is a constant. In this chapter, we shall denote any
such constant by C, with or without subscripts.
An immediate consequence of this second observation is the following simple result related to the
derivatives of constants in Section 11.1.
In other words, the antiderivatives of the zero function are precisely all the constant functions.
Indeed, many antiderivatives can be obtained simply by referring to various rules concerning deriva-
tives. We list here a number of such results. The first of these is related to the constant multiple rule
for differentiation in Section 11.2.
† This chapter was written at Macquarie University in 1999.
14–2 W W L Chen and X T Duong : Elementary Mathematics
CONSTANT MULTIPLE RULE. Suppose that a function f (x) has antiderivatives. Then for any
fixed real number c, we have
cf (x) dx = c f (x) dx.
ANTIDERIVATIVES OF POWERS.
(a) Suppose that n is a fixed real number such that n = −1. Then
1
xn dx = xn+1 + C.
n+1
(b) We have
x−1 dx = log |x| + C.
Proof. Part (a) is a consequence of the rule concerning derivatives of powers in Section 11.1. If x > 0,
then part (b) is a consequence of the rule concerning the derivative of the logarithmic function in Section
12.3. If x < 0, we can write |x| = u, where u = −x. It then follows from the Chain rule that
d du d 1 1
(log |x|) = × (log u) = − = (1)
dx dx du u x
again. ♣
Corresponding to the sum rule for differentiation in Section 11.2, we have the following.
SUM RULE. Suppose that functions f (x) and g(x) have antiderivatives. Then
(f (x) + g(x)) dx = f (x) dx + g(x) dx.
(b) We have
2
sec x dx = tan x + C and csc2 x dx = − cot x + C.
(c) We have
tan x sec x dx = sec x + C and cot x csc x dx = − csc x + C.
(d) We have
sec x dx = log | tan x + sec x| + C and csc x dx = − log | cot x + csc x| + C.
Proof. Parts (a)–(c) follow immediately from the rules concerning derivatives of the trigonometric
functions in Section 11.3. Part (d) follows from Example 12.3.12 and Example 12.3.13 if we note (1). ♣
Corresponding to the rule concerning the derivative of the exponential function in Section 12.3, we
have the following.
Chapter 14 : Introduction to Integration 14–3
Example 14.1.1. Using the sum rule, the constant multiple rule and the rule concerning antiderivatives
of powers, we have
1 3
(x2 + 3x + 1) dx = x2 dx + 3 x dx + x0 dx = x3 + x2 + x + C.
3 2
Example 14.1.2. Using the sum rule and the rules concerning antiderivatives of powers and of trigono-
metric functions, we have
1
(x3 + sin x) dx = x3 dx + sin x dx = x4 − cos x + C.
4
It follows that
1 − sin x
dx = 2 sec x dx − 2 tan x sec x dx − dx = 2 tan x − 2 sec x − x + C.
2
1 + sin x
We now discuss how we can use the chain rule in differentiation to help solve problems in integration.
This technique is usually called integration by substitution. As we shall not prove any result here, our
discussion will be only heuristic.
We emphasize that the technique does not always work. First of all, we have little or no knowledge
of the antiderivatives of many functions. Secondly, there is no simple routine that we can describe to
help us find a suitable substitution even in the cases where the technique works. On the other hand,
when the technique does work, there may well be more than one suitable substitution!
Remark. It is imperative that one does not give up when one’s effort does not seem to yield results.
We learn far more from indefinite integrals that we cannot find than from those than we can.
14–4 W W L Chen and X T Duong : Elementary Mathematics
2 5 2 3 2 2
= u − u + C = (x + 1)5/2 − (x + 1)3/2 + C.
5 3 5 3
On the other hand, if we make a substitution x = v − 1, then dx = dv, and
√
x x + 1 dx = (v − 1)v 1/2 dv = v 3/2 dv − v 1/2 dv
2 5/2 2 3/2 2 2
= v − v + C = (x + 1)5/2 − (x + 1)3/2 + C.
5 3 5 3
We can confirm that the indefinite integral is correct by checking that
d 2 2 √
(x + 1) − (x + 1) + C = x x + 1.
5/2 3/2
dx 5 3
Chapter 14 : Introduction to Integration 14–5
Remark. Note that in Version 1, the variable x is initially written as a function of the new variable
u, whereas in Version 2, the new variable u is written as a function of x. The difference, however, is
minimal, as the substitution x = g(u) in Version 1 has to be invertible to enable us to return from the
new variable u to the original variable x at the end of the process.
Note first of all that the derivative of the function x2 + 3 is equal to 2x, so it is convenient to make the
substitution u = x2 + 3. Then du = 2x dx, and
2 4 1 2 4 1 1 5 1 2
x(x + 3) dx = 2x(x + 3) dx = u4 du = u +C = (x + 3)5 + C.
2 2 10 10
Note first of all that the derivative of the function x3 is equal to 3x2 , so it is convenient to make the
substitution u = x3 . Then du = 3x2 dx, and
3 1 3 1 1 1 3
x2 ex dx = 3x2 ex dx = eu du = eu + C = ex + C.
3 3 3 3
3
A somewhat more complicated alternative is to note that the derivative of the function ex is equal to
3 3 3
3x2 ex , so it is convenient to make the substitution v = ex . Then dv = 3x2 ex dx, and
2 x3 1 2 x3 1 1 1 3
x e dx = 3x e dx = dv = v + C = ex + C.
3 3 3 3
Note first of all that the derivative of the function tan x is equal to sec2 x, so it is convenient to make
the substitution u = tan x. Then du = sec2 x dx, and
1 1
tan3 x sec2 x dx = u3 du = u4 + C = tan4 x + C.
4 4
14–6 W W L Chen and X T Duong : Elementary Mathematics
Occasionally, the possibility of substitution may not be immediately obvious, and a certain amount
of trial and error does occur. The fact that one substitution does not appear to work does not mean
that the method fails. It may very well be the case that we have used a bad substitution. Or perhaps
we may slightly modify the problem first. We illustrate this point by looking at two more examples.
Here it does not appear that any substitution will work. However, if we write
sin x
tan x dx = dx,
cos x
then we observe that the derivative of the function cos x is equal to − sin x, so it is convenient to make
the substitution u = cos x. Then du = − sin x dx, and
− sin x 1
tan x dx = − dx = − du = − log |u| + C = − log | cos x| + C.
cos x u
The formal definition of a definite integral is rather complicated, and we do not propose to discuss it
here. Instead, we shall only give some geometric motivation, and then relate the definite integral to
indefinite integrals we have discussed earlier.
Suppose that f (x) is a real valued function, defined on an interval [A, B] = {x ∈ R : A ≤ x ≤ B}.
We shall suppose also that f (x) has an antiderivative F (x) for every x ∈ [A, B].
Consider first of all the special case that f (x) ≥ 0 for every x ∈ [A, B]. By the definite integral
B
f (x) dx,
A
we mean the area below the curve y = f (x) and above the horizontal axis y = 0, bounded between the
vertical lines x = A and x = B, as shown in the picture below.
y
y = f(x)
x
A B
In general, we take the area between the curve y = f (x) and the horizontal axis y = 0, bounded
between the vertical lines x = A and x = B, with the convention that the area below the horizontal axis
y = 0 is taken to be negative, as shown in the picture below.
y = f(x)
x
A negative B
We now need a way of calculating this area. In some very special cases, this is very simple.
Example 14.3.1. If we examine the graph of the trigonometric functions in Chapter 3, then it is easy
to see that
2π π
sin x dx = 0 and cos x dx = 0.
0 0
In each case, it is easy to see that the area in question above the horizontal axis y = 0 is equal to the
area in question below this axis.
14–8 W W L Chen and X T Duong : Elementary Mathematics
Example 14.3.2. It is easy to see that the area between the line y = x and the horizontal axis y = 0,
bounded between the vertical lines x = 0 and x = 1, is the area of a triangle with base 1 and height 1.
Hence 1
1
x dx = .
0 2
In many instances, we do not have such geometric information to help us calculate the area in
question. Instead, we can use the indefinite integral.
Remark. A simple consequence of the above is that the constant multiple rule and sum rule for
indefinite integrals extend to definite integrals. For any fixed real number c, we have
B B
cf (x) dx = c f (x) dx.
A A
We also have
B B B
(f (x) + g(x)) dx = f (x) dx + g(x) dx.
A A A
A further consequence of the Fundamental theorem of integral calculus is a rule concerning splitting up
an interval [A, B] into two. Suppose that A < A∗ < B. Then
B A∗ B
f (x) dx = f (x) dx + f (x) dx.
A A A∗
and π
π
cos x dx = sin x = sin π − sin 0 = 0.
0 0
we have 1/2
1/2
1 −1 1 π
√ dx = sin x = sin−1 − sin−1 0 = .
0 1−x2
0 2 6
To obtain (6), recall that we can use the substitution x = sin u to show that
1
√ dx = du = u + C,
1 − x2
followed by an inverse substitution u = sin−1 x. Here, we need to make the extra step of substituting the
values x = 0 and x = 1/2 to the indefinite integral sin−1 x. Observe, however, that with the substitution
x = sin u, the variable x increases from 0 to 1/2 as the variable u increases from 0 to π/6. But then
π/6 π/6 1/2
π 1
du = u = = √ dx,
0 0 6 0 1 − x2
so it appears that we do not need the inverse substitution u = sin−1 x. Perhaps we can directly substitute
u = 0 and u = π/6 to the indefinite integral u.
Remark. If condition (b) above is replaced by the condition that the derivative g (u) < 0 for every u
satisfying β < u < α, then the same conclusion holds if we adopt the convention that
β α
f (g(u))g (u) du = − f (g(u))g (u) du.
α β
14–10 W W L Chen and X T Duong : Elementary Mathematics
we can use the substitution x = tan u, so that dx = sec2 u du. Note that tan 0 = 0 and tan(π/4) = 1,
and that sec2 u > 0 whenever 0 < u < π/4. It follows that
1 π/4 π/4 π/4
1 sec2 u π π
dx = du = du = u = −0= .
0 1 + x2 0 1 + tan2 u 0 0 4 4
we can use the substitution x = g(u) = u2 − 1, so that dx = 2u du. Note that g(1) = 0 and g(2) = 3,
and that g (u) = 2u > 0 whenever 1 < u < 2. It follows that
2
3 √ 2
2 5 2 3 64 16 2 2 62 14 116
x x + 1 dx = 2(u2 − 1)u2 du = u − u = − − − = − = .
0 1 5 3 1 5 3 5 3 5 3 15
Remark. If condition (b) above is replaced by the condition that the derivative h (x) < 0 for every x
satisfying A < x < B, then the same conclusion holds if we adopt the convention that
h(B) h(A)
g(u) du = − g(u) du.
h(A) h(B)
we can use the substitution u = h(x) = x2 + 3, so that du = 2x dx. Note that h(0) = 3 and h(1) = 4,
and that h (x) = 2x > 0 whenever 0 < x < 1. It follows that
1 4 4
1 1 u5 1 1024 243 781
2
x(x + 3) dx = 4 4
u dx = = − = .
0 2 3 2 5 3 2 5 5 10
Chapter 14 : Introduction to Integration 14–11
we can use the substitution u = h(x) = log x, so that du = h (x) dx, where h (x) = 1/x > 0 whenever
2 < x < 4. Note also that h(2) = log 2 and h(4) = log 4. It follows that
4 log 4 log 4
1 1 log 4
dx = du = log |u| = log log 4 − log log 2 = log = log 2.
2 x log x log 2 u log 2 log 2
we can use the substitution u = h(x) = sin x, so that du = cos x dx. Now h(0) = 0 and h(π) = 0, so
something is funny here! The problem is that
π
> 0 0<x< ,
2
h (x) = cos x π
< 0 <x<π .
2
before we can make any substitution. Consider now the first integral on the right hand side of (7). Using
the substitution u = h(x) = sin x, we note that h(0) = 0 and h(π/2) = 1, and that h (x) > 0 whenever
0 < x < π/2. Hence
π/2 1
1
sin2 x cos x dx = u2 du = .
0 0 3
Consider next the second integral on the right hand side of (7). Using the substitution u = h(x) = sin x,
we note that h(π/2) = 1 and h(π) = 0, and that h (x) < 0 whenever π/2 < x < π. Hence
π 0 1
1
2
sin x cos x dx = u du = −
2
u2 du = − .
π/2 1 0 3
Alternatively, we can make the substitution x = g(v) = π − v to the second integral on the right hand
side of (7). Then g(π/2) = π/2 and g(0) = π, and g (v) = −1 < 0 for every v satisfying 0 < v < π/2. It
follows that
π 0 π/2
2
sin x cos x dx = sin v cos v dv = −
2
sin2 v cos v dv.
π/2 π/2 0
14.4. Areas
We conclude this chapter by describing how we may use definite integrals to evaluate areas. Suppose
that the boundary of a region on the xy-plane can be described by a top edge y = g(x) and a bottom
edge y = f (x) bounded between two vertical lines x = A and x = B, as shown in the picture below.
y
y = g(x)
y = f(x)
x
A B
x2 y2
2
+ 2 = 1,
a b
where a, b ∈ R are positive, is equal to πab. To do this, we may consider the quarter of the ellipse in the
first quadrant, as shown in the picture below.
y
1/2
x2
y =b 1− 2
b a
x
a
We can use the substitution x = g(u) = a sin u. Then g(0) = 0 and g(π/2) = a. Furthermore, we have
dx = g (u) du, where g (u) = a cos u > 0 whenever 0 < u < π/2. It follows that
a 1/2 π/2 π/2
x2
b 1− 2 dx = ab(1 − sin2 u)1/2 cos u du = ab cos2 u du
0 a 0 0
π/2 π/2
1 1 1 1 πab
= ab + cos 2u du = ab u + sin 2u = .
0 2 2 2 4 0 4
Chapter 14 : Introduction to Integration 14–13
Example 14.4.2. We wish to evaluate the area of the triangle with vertices (0, 1), (1, 0) and (3, 2). To
do this, we split the triangle into two regions as shown in the picture below.
y
2
1 2 3 x
The triangle on the left is bounded between the vertical lines x = 0 and x = 1, and the top edge and
the bottom edge are given respectively by
1
y= x+1 and y = 1 − x.
3
The triangle on the right is bounded between the vertical lines x = 1 and x = 3, and the top edge and
the bottom edge are given respectively by
1
y= x+1 and y = x − 1.
3
It follows that the area of the original triangle is given by
1 3
1 1
x + 1 − (1 − x) dx + x + 1 − (x − 1) dx
0 3 1 3
1 3 1 3
4 2 2 2 1
= x dx + 2 − x dx = x + 2x − x2 = 2.
0 3 1 3 3 0 3 1
Example 14.4.3. We wish to evaluate the area of the quadrilateral with vertices (1, 1), (2, 0), (4, 1)
and (3, 5). To do this, we split the quadrilateral into three regions as shown in the picture below.
y
5
1 2 3 4 x
The triangle on the left is bounded between the vertical lines x = 1 and x = 2, and the top edge and
the bottom edge are given respectively by
y = 2x − 1 and y = 2 − x.
14–14 W W L Chen and X T Duong : Elementary Mathematics
The quadrilateral in the middle is bounded between the vertical lines x = 2 and x = 3, and the top edge
and the bottom edge are given respectively by
1
y = 2x − 1 and y= x − 1.
2
The triangle on the right is bounded between the vertical lines x = 3 and x = 4, and the top edge and
the bottom edge are given respectively by
1
y = 17 − 4x and y= x − 1.
2
It follows that the area of the original quadrilateral is given by
2 3 4
1 1
((2x − 1) − (2 − x)) dx + (2x − 1) − x−1 dx + (17 − 4x) − x−1 dx
1 2 2 3 2
2 3 4
3 9
= (3x − 3) dx + x dx + 18 − x dx
1 2 2 3 2
2 3 4
3 2 3 9 15
= x − 3x + x2 + 18x − x2 = .
2 1 4 2 4 3 2
Alternatively, we can transpose the picture above and split the quadrilateral into two regions as shown
in the picture below:
x
y
1 2 3 4 5
Note that the roles of x and y are now interchanged. The triangle on the left is bounded between the
vertical lines y = 0 and y = 1, and the top edge and the bottom edge are given respectively by
x = 2y + 2 and x = 2 − y.
The triangle on the right is bounded between the vertical lines y = 1 and y = 5, and the top edge and
the bottom edge are given respectively by
17 1 1 1
x= − y and x= y+ .
4 4 2 2
It follows that the area of the original quadrilateral is given by
1 5
17 1 1 1
((2y + 2) − (2 − y)) dy + − y − y+ dy
0 1 4 4 2 2
1 5 1 5
15 3 3 2 15 3 15
= 3y dy + − y dy = y + y − y2 =
0 1 4 4 2 0 4 8 1 2
as before.
Chapter 14 : Introduction to Integration 14–15
2. Evaluate each of the following indefinite integrals using the given substitution:
a) x(x2 − 1)99 dx (use the substitution u = x2 − 1)
x2
b) √ dx (use the substitution u = x3 + 2)
2 + x3
c) sin 4x dx (use the substitution u = 4x)
dx
d) (use the substitution u = 2x + 1)
(2x + 1)2
x+3
e) dx (use the substitution u = x2 + 6x)
(x2 + 6x)2
f) sec ax tan ax dx (use the substitution u = ax)
6. Use definite integrals to find the area between the curves y = ex and y = e2x , bounded between the
lines x = 0 and x = 1.
7. Find the area of the triangle with vertices (0, 0), (4, 3) and (1, 5).
8. Find the area of the quadrilateral with vertices (1, 1), (5, 2), (2, 3) and (4, 3).
− ∗ − ∗ − ∗ − ∗ − ∗ −